Cognitive and emotional aspects presented in victims of victms and perpetrators of bullying (Revista de Investigaciones Universidad del Quindío, 2015)
This article is based on a research that aims to describe the emotional cognitive characteristics of eighth grade students an educational institution of La Tebaida, Quindío, involved in the phenomenon of bullying as victims and perpetrators. For to obtain information employed a quantitative methodology – descriptive, the information was collected by applying individual questionnaires.
Keywords: cognition; emotion; aggressor; victim; bullying